Rethinking Public Relations Campaigns as a Strategic Tool for Tourism Promotion in Taraba State: A Conceptual Approach - Gambo, Sarah; Danjuma, Mercy (Darul Yasin Al Sys, 2025)
Tourism has become a critical driver of economic growth, cultural exchange, and community development, yet Taraba State, despite its rich natural and cultural resources, remains one of Nigeria’s least promoted tourist destinations. This conceptual paper examines how public relations (PR) can be reimagined as a strategic instrument for advancing tourism promotion in Taraba State. Drawing on Strategic Communication Theory and Destination Image Theory, it develops a conceptual model that integrates four interrelated components: strategic communication, destination branding, stakeholder engagement, and integrated media application. Through a synthesis of literature on tourism communication, destination branding, and stakeholder collaboration, the paper argues that effective PR extends beyond mere publicity to strategically shape perceptions, reinforce destination identity, and cultivate sustainable relationships among key stakeholders. It further highlights how coordinated PR strategies, supported by integrated media that combine traditional and digital platforms, can enhance destination visibility, foster two-way communication, and sustain audience engagement, thereby positioning Taraba as a recognised and competitive tourism hub. The paper concludes that institutionalising tourism communication policy, strengthening public–private partnerships, and implementing sustainable, culturally grounded PR campaigns are essential for repositioning Taraba’s tourism sector, and that the proposed, theoretically grounded framework tailored to the Nigerian context contributes to scholarly and practical debates on the role of public relations in tourism development in emerging destinations.